Sosyal Medyanın Karanlık Yüzü - Ersöz Karakulakoğlu, Selva (The Turkish Online Journal of Design Art and Communication, 2012)
In this century, which we name as digital age, the information has being shown as numbers. Without a doubt, the internet has made a huge contribution to the structuring of digital process. Especially the social media, which has been in our lives since the mid-2000s, differentiated doing politics and transported it into the internet. Social media tools, alleged to be more democratic, more transparent, and more interactive, have received wide acclaim during the entire process. Within these tools which bring visuality in the foreground, the insurgencies are more romantic, elections campaigns are more colorful, and the protest actions are more attractive. In these terms, social media have been exalted regarding social participation and facility of organization. When we look at the other side, these freedom promising tools, in fact, shelter a market worth billions of dollars behind. Is social media really a tool for freedom and progress? What lies beneath the back side of this market? Are the work of amateur spirit which is developing on the internet is of poor quality? Is Facebook really affective during the so-called ‘Arab Spring’? From a critical point of view, this study aims to discuss the back and unseen side of social media. The theoretical framework will be based on the internet culture and the transformation of this culture in itself (Lovink, 2007) and YouTube, Facebook, Twitter, blogs and Wikipedia which are the part of internet culture and our visual culture since the mid-2000s, will be analyzed and what these tools really serve for will be discussed. As noted by internet critic Carr, " All the things Web 2.0 represents - participation, collectivism, virtual communities, amateurism - become unarguably good things, things to be nurtured and applauded, emblems of progress toward a more enlightened state. But is it really so? "(2005).
Keywords: Internet Culture; Social Media; İnternet Kültürü; Sosyal Medya